Navigating Sustainability A Bibliometric Analysis Of Carbon Management Accounting - Nazaria, Md. Aris; Sofiah, Md Auzair; Norman, Mohd Saleh; Maizatulakma, Abdullah (UNIMAS Publisher, 2025)
In the era of increasing concerns over climate change and sustainable development, Carbon Management Accounting (CMA) research gains paramount attention. Previous studies focused on specific aspects of carbon accounting, leaving a gap in comprehensive exploration of CMA's holistic approach to sustainability challenges. This study aims to provide a comprehensive overview of the current state of CMA research and its implications for sustainability efforts. Bibliometric and network analyses, utilizing Harzing's Publish or Perish (PoP) and VOSviewer (VOS) software, 200 Scopus-indexed documents from 2013 to 2022 were examined. Performance analysis, citation analysis, journal analysis, and network analysis were employed to examine the field from research practice and system perspectives. From a practice-perspective, the analysis reveals CMA research as an "advancement," depicting progressive, impactful, and dynamism within the field. The system-perspective displays a “transformative” role characterized by prominence, synergy, and integration. Popular themes among researchers and countries include keywords like "carbon," "carbon accounting," "environmental policy," and "climate change." A significant gap between sustainability development and the carbon accounting model in CMA is identified, emphasizing the need for further integrated research. This study is pivotal for practitioners, policymakers, and researchers, aiding sustainability efforts and addressing global climate change.